Transcendentalism Reflected in Emerson’s Poem Brahma - Zhang, Jingling; Zheng, Peiwei (International Journal of English Literature and Social Sciences (IJELS), 2019)
Brahma is one of Emerson’s famous lyric poems, in which Emerson, assuming the role of Brahma, expresses his idea that human beings can perfect themselves morally and spiritually only through the realization of the Brahman. This article is a tentative study of the poem in terms of its artistic form and its connotation from the perspective of Transcendentalism.